Study on Efficiency of Herb Extracts to Inhibit Enteric Bacteria and Application of Jerusalem artichoke as a Prebiotic for Yogurt Production - สิทธิ์เหล่าถาวร, กานต์ชนา; เดชกล้า, มนัสวี (Journal of Food Health and Bioenvironmental Science, 2017)
The aim of this research was to study the activity of herb plant extracts (Garcinia cowa Roxb., Syzygium cumin L., Psidium guajava L., Solanum torvum Sw. and Ageratum conyzoides L.) against enteric bacteria growth. Antibacterial activities were determined by agar-well diffusion method against Escherichia coli, Staphylococcus aureus and Salmonella Typhimurium. Garcinia cowa Roxb. extract against E. coli showed the highest efficacy with inhibition zone of 2.31±0.22 cm. diameter, zone against S. aureus and S. Typhimurium equalled 1.77±0.00 cm and 1.45±0.04 cm diameter, respectively. Psidium guajava L. and Syzygium cumin L. extracts against only S. aureus. No Inhibition zones were observed for Solanum torvum Sw. and Ageratum conyzoides L. extracts. An extract of Garcinia cowa Roxb. was added into yogurt, the Garcinia cowa Roxb. extract increased growth of Lactobacillus bulgaricus and Streptococcus thermophilus by 18.25 % and 22.56%, respectively when compared to plain yogurt (12.00-13.97%). An 80 μl extract of yogurt (mixed Garcinia cowa Roxb.) inhibited growth of E. coli and S. aureus. To evaluate properties of Fructo-oligosaccharide extracted from Jerusalem artichoke (Helianthus tuberosus L.) by 10% Jerusalem artichoke extract was added into yogurt. No difference were observed for growth rate of L. bulgaricus and S. thermophilus, no differences were observed between plain yogurt and Jerusalem artichoke yogurt but Jerusalem artichoke extract promoted growth of L. bulgaricus and S. thermophilus when it was used instead of dextrose in MRS broth as a carbon source. The results indicated that Garcinia cowa Roxb. extract is appropriate to use as a supplement in yogurt to efficiently increase the inhibition of enteric bacteria growth.